Navigating Complexity of Serving Displaced Communities: A Study of Yemeni Community-Based Organizations in Egypt - Al-Mahdi, Alya Mohammed (AUC Knowledge Fountain, 2023)
Forced displacement is a global crisis that poses challenges for nations like Egypt. Despite international NGO support, escalating displaced individuals have overwhelmed existing capacities. Refugee Community-Based Organizations (CBOs) have emerged as a natural response from the communities themselves to bridge the gap between the state and NGOs and the refugee community. However, CBOs in Egypt face challenges that impact their operation and continuity. Through qualitative research, this study aims to explore the experience of the Yemeni CBOs. Through interviews with seven people from six CBOs conducted through field visits and online calls, this research uncovers the dynamics of Yemeni CBOs within Egypt's humanitarian community. It explores their role in providing awareness, support, and the necessary assistance. The findings reveal that Yemeni CBOs emerged in response to the influx of Yemeni refugees to Egypt in 2015, driven by the challenges faced by the Yemeni community. These organizations play a crucial role especially during the pandemic when access to traditional relief agencies was limited. However, despite their essential functions, Yemeni CBOs encounter significant challenges, including the complexities of legal registration, which lead to financial constraints, administrative and operational challenges, and tensions with both the host and displaced communities while showcasing their adaptability and resilience strategies. These insights concluded with recommendations aimed at key stakeholders, including the Egyptian government, UNHCR, other NGOs providing services, and the Yemeni CBOs and community. This study contributes to the broader discourse on effective community-driven strategies and interventions that ensure the recent participatory approach called by the UNHCR.